Analisis Sistem Informasi Inventory Menggunakan Metode Single Moving Averange Pada PT. Inkolanggeng Makmur Jakarta - Betaria Safitri; Savira Dwi Gustina; Reynaldi Abdillah; Eka Wulansari Fridayanthie; Rifky Permana (Jurnal Insan, 2023)
Abstracts - With the advancement of information technology, the need for fast, accurate, and precise information access has become increasingly crucial. Therefore, companies must have efficient computerized systems to support their business processes. The issue at PT. INKOLANGGENG MAKMUR in the warehouse department is that the recording of incoming and outgoing goods is still done manually, which is time-consuming and prone to errors. By using an inventory system, users have the ability to organize and control the necessary information. For example, they can view, add, store, modify, and delete data. Additionally, this system can also predict the quantity of goods needed to be purchased for the next period and control the activities of expenditure and receipt of goods. The author utilizes the single moving average method to facilitate forecasting regarding stock inventory.